MENINGKATKAN PROSES DAN HASIL BELAJAR TEMATIK MENGGUNAKAN MODEL PEMBELAJARAN PREDICT, OBSERVE, EXPLAIN KELAS V SEKOLAH DASAR - Hamzah, Iri; Apdoludin, Apdoludin; Subhanadri, Subhanadri; Eko Putra, Adryan (Jurnal Muara Pendidikan, 2024)
The problem in this study stems from the number of students who are still passive in teaching and learning activities in the classroom, the absence of creative, innovative, interesting and fun learning models. This study aims to describe the improvement of the process and student learning outcomes.This research is a class action research. The research subjects were fifth grade students of SD Negeri 202/II Simpang Tebat. In its implementation, this research consisted of two cycles conducted by the researcher. Each cycle consists of planning activities, action implementation, observation and reflection. The results of this study indicate that the use of the Predict, Observe, Explain learning model can improve the process and learning outcomes of students. This can be seen from the performance process of educators in cycle I with an average percentage of (60%) in the sufficient category and cycle II with an average percentage of (83%) in the very good category. The learning process of students in cycle I with an average percentage of (27%) in the failure category and in cycle II with an average percentage of (100%) in the excellent category. For the Minimum Completion Criteria standard of 70, this can be seen from the completeness of the learning outcomes of students in cycle I with a percentage of (70.67%) with a good category and cycle II with a percentage of (85.33%) with a very good category that reaches KKM.